Effects of Money Politics on Party Primaries in Nigerian 2019 General Election: Reflections on All Progressives Congress (APC) and People's Democratic Party (PDP) - Babayo Sule (UIN Sunan Gunung Djati, 2022)
Money politics has become an acceptable norm and a part of Nigerian political culture before and after the conduct of general elections since the resurgence of the democratic rule in the Fourth Republic (1999). The nature and dimension of money politics have taken a new picture in Nigerian politics during the party primaries in preparation for the 2019 General Election, particularly between the two major contending parties; the All Progressives Congress (APC) and the Peoples Democratic Party (PDP) who were involved in excessive use of money unprecedented in the history of Nigerian politics during the party primaries in September and October 2018. This work investigated the role of money in determining the outcome of party primaries in Nigeria in the ruling APC and the major opposition PDP and how it will affect the General Election in 2019. The research used a quantitative method of data collection and analysis. Both the primary and secondary sources were used during the conduct of the research. The data obtained were grouped in a thematic form where a simple tabular percentage was used for interpretations and results. The research discovered that there was an extraordinary deployment of money from the state-owned resources by politicians to arrest their campaign expenses and political ambition. In the process, vote-buying and excessive spending violated the electoral process and deprived the electorates of getting credible candidates in the parties' primaries. The research recommends that there is a need for a more aggressive and severe sanction on all politicians that are found in this evil act. The work also realized the serious need for massive public enlightenment on the evil of money politics.